Activation of the IGF1 receptor stimulates glycogen synthesis by mink uterine epithelial cells. Issue 5 (23rd April 2018) - Dean, Matthew; Rose, Jack
Abstract : Glycogen synthesis by mink uterine epithelial cells is stimulated by estradiol (E2 ) during estrus, although the mechanism/s through which the steroid promotes glycogen accumulation are unknown. Our aim was to determine if insulin is required for E2 induced glycogen synthesis by an immortalized mink uterine epithelial cell line (GMMe). We show that the cells expressed the genes for glycogen metabolizing enzymes (hexokinase 1, glucose‐6‐phosphatase 3, glycogen synthase 1, and glycogen phosphorylase‐muscle), receptors for insulin, insulin‐like growth factor 1 and E2 ( Esr1 ). Interestingly, treatment of cells with E2 alone failed to stimulate glycogen production, whereas supraphysiological concentrations of insulin (50 μg/ml) only, significantly increased glycogen content. Moreover, insulin + E2 increased glycogen content when compared to insulin alone ( p < 0.05), an affect that was blocked when cells were treated with the pure E2 receptor antagonist ICI 182, 780. Glycogen synthesis in response to insulin was significantly inhibited when cells were pre‐treated with picropodophyllotoxin, an IGF1R antagonist. Treatment of cells with LY294002, a phosphatidylinositol 3‐kinase (PI3K) antagonist, blocked insulin's effects on glycogen production whereas treatment with U0126, an inhibitor of mitogen activated kinase‐kinase (MEK1/2) was without effect. These findings suggest to us that the affects of E2 on glycogen synthesis by GMMe cells is mediated through Esr1 and increased responsiveness of the cells to insulin. Because picropodophylotoxin blocked the effects of insulin on glycogen production, and both insulin and IGF1 act through PI3K, it is possible that IGF1 plays a role in glycogen production by these cells.